PENGARUH KOMPOS AMPAS SAGU DAN PLANT GROWTH PROMOTION RHIZOBACTERIA (PGPR) TERHADAP PERTUMBUHANDAN HASIL KACANG TANAH (Arachis hypogeal L.) - Saerah Adam; Mochamad Dawam Magfoer; Didik Haryono (BUANA SAINS, 2018)
The aims of this research is to find out the influence of the application of sago waste compost and PGPR on the increase in groundnut growth and yield and to obtain the dose of sago waste compost and PGPR concentration that able to increase the growth and yield of groundnut had been conducted in January to March 2016 in Maba Sangaji Village, Kota Maba Subdistrict, East Halmahera Regency. The research used factorial randomized complete block design consisting of two factors with three replication. Factor I was the dose of sago waste compost consisted of four levels: K0 = without sago waste compost (control), K1 = sago waste compost of 10 t ha-1, K2 = sago waste compost of 15 t ha-1, and K3 = sago waste compost of 20 t ha-1. Factor II was concentration of Plant Growth Promoting Rhizobacteria (PGPR) consisted of 4 levels: P0 = without PGPR (control), P1 = PGPR of 5 ml l-1, P2 = PGPR of 10 ml l-1, and P3 = PGPR of 15 ml l-1. The observation consisted of growth components of plant height, the number of leaves, leaf area, crop dry weight, and crop growth rate, and yield components of the number of pods, filled pods, empty pods, pod weight, grain weight, and weight of 100 grain. Research result shows that there was no interaction between the treatment of sago waste compost and PGPR. However, separately, treatments of sago waste compost and PGPR had the significant influence on the growth and yield of groundnut. The highest groundnut yield was obtained in the treatment of sago waste compost with the dose of 20 t ha-1. Grain weight obtained was 17.51 g or an increase of 52.15% compared to those of treatment without application of sago waste compost and yield of grain weight per hectare was 2.80 t ha-1. The inoculation of PGPR increased the growth and yield of groundnut. The application of PGPR with the concentration of 10 and 15 ml-1 produced better crop growth. The higher result was obtained in the treatment of PGPR with the concentration of 10 and 15 ml l-1with grain weight of 15.46 g and 16.81 g plant-1 or an increase of 31.15% and 42.6%, respectively, compared to control,whereas, grain weight per hectare was 2.47 t ha-1 and 2.69 t ha-1, respectively.